Impact of Maltodextrin and Inulin on Synbiotic Fermented Milk Production - Reda Mohamed El-Komaily; Osama Elbatawy; Ihab Aumara (Arab Universities Journal of Agricultural Sciences, 2022)
The influence of maltodextrin or inulin added as a prebiotic on the survival of various strains of probiotics in synbiotic fermented milk along cold storage was investigated. Synbiotic fermented milk was prepared using several probiotic strains (Lb. helveticus and Lb. acidophilus) and 2% maltodextrin or inulin and compared with traditional yoghurt starters (Lb. delbrueckii subsp. bulgaricus and Str. thermophilus). Synbiotic fermented milk samples were stocked at 4°C then the chemical, microbiological and sensory characteristics were estimated. Starter culture strains showed no significant effect on dry matter and ash contents in various synbiotic fermented milk samples during storage. However, starter culture type, fortification by maltodextrin or inulin, and storage period significantly influenced the acidity, total and soluble nitrogen contents (SN\TN), acetaldehyde, diacetyl contents and viscosity in various synbiotic fermented milk samples. In addition, fortification of maltodextrin or inulin significantly influenced the survival of yoghurt starter culture strains, Lb. helveticus and Lb. acidophilus strains. The counts of probiotic strains used in all treatments of synbiotic fermented milk survived well and were above the recommended minimum levels (106CFU/ mL) during a storage period.